2003
DOI: 10.1074/jbc.m300129200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Interactions and Bifunctionality Make the Response of Glutamine Synthetase Cascade System of Escherichia coli Robust and Ultrasensitive

Abstract: Glutamine synthetase (GS) regulation in Escherichia coli by reversible covalent modification cycles is a prototype of signal transduction by enzyme cascades. Such enzyme cascades are known to exhibit ultrasensitive response to primary stimuli and act as signal integration systems. Here, we have quantified GS bicyclic cascade based on steady state analysis by evaluating Hill coefficient. We demonstrate that adenylylation of GS with glutamine as input is insensitive to total enzyme concentrations of GS, uridylyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
7
32
0
Order By: Relevance
“…Covalent modification cycles that are catalyzed by one bifunctional "ambiguous" enzyme rather than by two independent converter proteins cannot have high-level responses, because high substrate concentrations and low product concentrations for both reactions of the cycle are inconsistent (106). Paradoxically, in another theoretical study, bifunctionality (among other factors) was considered essential for ultrasensitivity (638).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent modification cycles that are catalyzed by one bifunctional "ambiguous" enzyme rather than by two independent converter proteins cannot have high-level responses, because high substrate concentrations and low product concentrations for both reactions of the cycle are inconsistent (106). Paradoxically, in another theoretical study, bifunctionality (among other factors) was considered essential for ultrasensitivity (638).…”
Section: Downloaded Frommentioning
confidence: 99%
“…A steady-state analysis of adenylylation of GS with glutamine as the input in a model of the GS bicyclic cascade (UTase-ATase-GS) demonstrated an ultrasensitive response; it was concluded to be brought about by allosteric interactions of glutamine and 2-oxoglutarate, bifunctionality of converter enzymes, and a closed-loop bicyclic cascade structure (638). In a follow-up study, a steady-state modular analysis of a network made up of the above-mentioned GS bicyclic closed-loop cascade, together with the NRII-NRI twocomponent system and an autoregulated glnALG operon, was presented.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In many bacteria, ATase catalyzes the adenylylation of a Tyr side chain on each GS subunit, and this, in turn, decreases the catalytic activity of GS as described initially by Stadtman and co-workers (Refs 20 and 21 and Fig. 1) and elaborated by others (22). The ATase reaction is highly specific for GS; no other substrates for ATase have been identified or suggested.…”
mentioning
confidence: 96%
“…We will still refer to AT and AR when discussing the modification of GS, however; in equations (1)–(3) we simply set [AR] = [PII-UMP] and [AT] = [PII]. This is roughly equivalent to the model of Mutalik et al [13] with tight binding of AR to PII-UMP and of AT to PII and with the concentration of AT/AR substantially in excess of PII/PII-UMP. Here we are ignoring the effects of ATP and α -KG [25] on these interactions.…”
Section: Modelsmentioning
confidence: 99%
“…They found that while the glutamine pool could fluctuate significantly in response to changes in the ammonium concentration, the total flux of nitrogen into the cell (via glutamine and glutamate) remained relatively constant at steady state regardless of the external ammonium concentration. Mutalik et al [13] found that the bicyclic cascade with totally unsaturated enzymes responded to changes in the ammonium concentration with a consistent level of sensitivity (as measured by Hill coefficient), regardless of small variations in parameters. However, they did not include the effects of feedback in their model.…”
Section: Introductionmentioning
confidence: 99%